Implementasi Manajemen Bisnis Syariah Dengan Prinsip Actuating Pada Umkm Kuliner Kampus di Kantin Asrama Universitas Truno Joyo Madura - Hazmatul Khumairo'; Elza Luthfiyah; Nur Fatihatun Nisa’; Muhammad Bagus Junaidi; Siti Zubaidah (Iltizam : Jurnal Ekonomi dan Keuangan Islam, 2026)
Sharia management in the business world emphasizes the application of Islamic values that are in line with business objectives, one of which is through the principle of actuating that focuses on mobilizing and motivating human resources. The application of this principle can be observed in the practice of campus culinary MSMEs, particularly the Mr. A Canteen at the Trunojoyo University of Madura Dormitory. Since its establishment in 2014, this canteen has been able to survive for more than a decade with a simple but effective strategy, namely personal capital without usury, friendly service, affordable prices, and guaranteed halal products. This study uses a descriptive qualitative method with a case study approach through interviews and direct observation. The results show that the actuating principle is reflected in the involvement of family members as workers, harmonious work management, and service strategies that build customer loyalty. These efforts show that resource mobilization is carried out not only for economic gain but also for the sake of business blessings in accordance with sharia guidance. The application of sharia management in Mr. A canteen MSME provides evidence that the actuating principle can be implemented in small businesses. The integration of spiritual values and daily business practices makes this business not only economically beneficial but also supports the creation of competitive halal businesses.